Analisis Berfikir Tingkat Tinggi Siswa pada Materi Hukum Ke-2 Termodinamika - Safutra, Yosie; Linuwih, Suharto (UPEJ Unnes Physics Education Journal, 2021)
The purpose of this study was to analyze students' higher-order thinking on the material of the 2nd law of Thermodynamics. The subjects of this study were grade 12 students of SMAN 1 Jakenan for the academic year 2020/2021 as many as 127 students who had taken physics lessons on the material of the 2nd law of Thermodynamics. The selection of students using snowball sampling technique. The method of data collection in this study used a question instrument, and interviews. Based on the data from the test results, the researchers calculated the validity and reliability. Interviews are used to find out how students think further in solving problems. Interviews were only conducted to 15 students who were selected from the categories of high, medium, and low ability students based on the test results that had been given. The data analysis technique used is the Miles and Huberman model data analysis technique which includes three simultaneous activities: (1) data reduction (2) data presentation, and (3) conclusion drawing (verification). Based on the data analysis and discussion in this study, it can be concluded that the instrument used is a set of higher-order thinking ability assessment instruments to measure higher-order thinking skills in the form of 6 two-tier multiple choice questions and is given online due to the Covid-19 pandemic. Based on the validity and reliability tests, the content validity of the developed higher order thinking skills assessment instrument has a very decent category. The empirical validity of 100% of the questions is declared valid. The question instrument developed has declared reliable with high criteria. Based on the analysis that has been done, it can also be concluded that students who have high-level thinking skills and are able to solve existing problems correctly and are able to explain them. Meanwhile, students who have low-level thinking skills cannot answer correctly, only guess and do not know how to do it.